DESEMPENHO DE NOVILHOS EM PASTEJO RECEBENDO 25-OH VITAMINA D3 NA RECRIA E TERMINAÇÃO - Fernanda Simões Mudado (2022)
Brazil has the largest commercial herd in the world, with most of beef production on pastures. One of the most used technologies used for intensification of production systems is supplementation, however, different types of supplements can be used depending on animal category, pasture composition and objective. It is also possible to combine the use of supplements with additives for better responses, making the strategy more economically efficient. Among the available additives for ruminant production, monensin is the most used additive and aims to improve animal performance and feed efficiency. However, trade barriers and market requirements regarding the use of antibiotics make necessary the study of alternatives to antibiotic additives. In this way, the objective with the present study was to evaluate the effect of 25-OH Vit D3 for growing and finishing grazing Nellore young bulls on performance, body measures and carcass characteristics. In Experiment 1, one hundred and fifty animals with an average body weight (BW) of 300 ± 23 kg were used. Treatments consisted of a protein supplement (Fosbovi® Proteico 30, DSM, Brazil), with or without Sodium Monensin (320 mg/kg) or a protein-energetic supplement (Fosbovi® proteico-energico 25, DSM, Brazil); all supplements were evaluated with or without the addition of 25-OH Vit D3 (Hy-D®, DSM, Brazil), in a dose adjusted to daily intake of 1 mg/animal. In Experiment 2, two hundred and forty animals with an average body weight (BW) of 390 ± 16 kg were used. Treatments consisted of the same protein-energetic supplement used in Experiment 1. Animals receiving different treatments in Experiment 1 had similar AGD and final BW (P>0.05). The addition of monensin in the protein supplement reduced growth of body measures (P<0.05), except for the growth of height at withers (P>0.05). Animals that received 25-OH Vit D3 in the protein-energetic supplement had greater growth of the rib width (P<0.05). In Experiment 2, animals that received 25-OH Vit D3 weighed 8.0 kg more (P<0.05) and had 8.0 kg higher HCW (P<0.05). Differences found in the responses of experiments 1 and 2, are possible due interactions of the animal´s growth curve and 25-OH Vit D3 anabolic effects. For finishing beef cattle on grazing, supplementation with 25-OH Vit D3 presents a promising technology for beef producers, improving carcass gain and yield.